2019
DOI: 10.18087/cardio.2019.8.n534
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary congestion by lung ultrasound in decompensated heart failure: associations, in-hospital changes, prognostic value

Abstract: Background. Recently lung ultrasound (LUS) based on B-lines measurement has been proposed as an effective tool for assessment of pulmonary congestion (PC) in patients with decompensated heart failure (DHF).Objective: to assess the incidence, in-hospital changes and prognostic significance of PC assessed by LUS in DHF patients.Materials and methods. Routine clinical assessment and eight-zone LUS were performed in 162 patients with DHF (men 66%, mean age 68±12 years, hypertension 97%, history of myocardial infar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
6
0
6
Order By: Relevance
“…The prognostic significance of the number of B-lines varied across studies. Most studies indicated that a sum of ≥5 B-lines was associated with a higher probability of 12-month all-cause death, and ≥15 B-lines with higher probability of HF readmission [45,[50][51][52]56,61,65]. Others [57] suggested that the presence of 30-40 B-lines at admission was a risk factor for readmission or mortality, and the presence of ≥15 B-lines could indicate just an increased risk of persistent pulmonary congestion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The prognostic significance of the number of B-lines varied across studies. Most studies indicated that a sum of ≥5 B-lines was associated with a higher probability of 12-month all-cause death, and ≥15 B-lines with higher probability of HF readmission [45,[50][51][52]56,61,65]. Others [57] suggested that the presence of 30-40 B-lines at admission was a risk factor for readmission or mortality, and the presence of ≥15 B-lines could indicate just an increased risk of persistent pulmonary congestion.…”
Section: Resultsmentioning
confidence: 99%
“…However, mortality was associated to significantly lower IVC collapse [65,70,71], and a greater number of lung B-lines; and higher NT-proBNP levels [65,[68][69][70] without differences in the BIA parameters. Among the most individuals with ambulatory follow-up and preserved ejection fraction [66,73], the submaximal exercise increases B-lines number to level of higher probability of 12-month all-cause death or/ and higher probability of HF decompensation [45,[50][51][52]56,61]. Total Bline sum correlated significantly, although moderately, with congestion and several inflammation biomarkers.…”
Section: Risk Of Readmission and Mortality With 3month Follow-upmentioning
confidence: 95%
“…Experts’ comments [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 ,…”
Section: Recommendationsunclassified
“…В 2004 г. Е. Picano и Jambrik в лаборатории эхокардиографии Института клинической физиологии Национального научно-исследовательского совета Италии перенесли УЗИ легких из отделения интенсивной терапии в отделение кардиологии, описав корреляцию между содержанием внесосудистой жидкости в легких, оцененной с помощью рентгенографии грудной клетки, и количеством B-линий, обнаруженных при УЗИ легких [18]. В последующие годы была предоставлена экспериментальная [9,19], клиническая [20][21][22][23] и методологическая [24] валидация B-линий.…”
Section: введение и исторические предпосылкиunclassified